2021
DOI: 10.20448/journal.509.2021.82.206.215
|View full text |Cite
|
Sign up to set email alerts
|

Spelling Mastery via Google Classroom among Year 4 Elementary School ESL Students during the COVID-19 Pandemic

Abstract: Spelling mastery is an important prerequisite of proficiency in the English language. The conventional language teaching strategy needs to be revolutionized for the 21st century by utilizing Information and Communication Technology (ICT) to enable English as a Second Language (ESL) students to master spelling. As such, online teaching and learning becomes a crucial strategy to impart and receive knowledge. This case study focused on teaching spelling mastery via Google Classroom to elementary school ESL studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Several Positive effects on academic performance were found in any educational type of intervention compared to those who did not receive interventions or before exposure to interventions. Academic-related behavior outcomes such as engagement or motivation had positive effects in synchronously student-centered interventions [20,25,30,41], while other interventions produced a mix of positive and negative results. Difficulties with remote or distance education in all studies were mostly associated with technical issues such as screens freezing or the inability of the school's infrastructure to support the platform's operations [22,23,26,27].…”
Section: Intervention Outcomesmentioning
confidence: 98%
See 3 more Smart Citations
“…Several Positive effects on academic performance were found in any educational type of intervention compared to those who did not receive interventions or before exposure to interventions. Academic-related behavior outcomes such as engagement or motivation had positive effects in synchronously student-centered interventions [20,25,30,41], while other interventions produced a mix of positive and negative results. Difficulties with remote or distance education in all studies were mostly associated with technical issues such as screens freezing or the inability of the school's infrastructure to support the platform's operations [22,23,26,27].…”
Section: Intervention Outcomesmentioning
confidence: 98%
“…consisted of exercises or discussions where students received real-time feedback through Snappet and Google classroom [30,41]. The asynchronously student-centered approach was presented via gamification or exercises where students were given flexible learning times such as the Science Level Up program [32].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…In terms of English classroom instructions, an extensive number of studies have been conducted to investigate the use of LMS in at various education levels (Al-Khresheh, 2022;Maulana & Lintangsari, 2021;Rasmitadila et al, 2020;Sefriani et al, 2021;Tarteer et al, 2021;Yen & Mohamad, 2021). These studies reported that Edmodo, Blackboard, Moodle, Google Classroom, and other LMSs are extensively used to enhance the blended and online learning during the pandemic.…”
Section: Introductionmentioning
confidence: 99%